Developing Digital Library “Komulit” Application Using Kodular for Enriching Students’ Reading References - Rachmawati, Amalia; Setiawan, Slamet; Mustofa, Ali (Jayapangus Press, 2024)
In the current massive digital development, we have to face the fact that our students are more engaged with their smartphones rather than books. However, some schools have no facilities to provide digital reading sources and they also lack of book collections. This study aims to develop a library application to provide students with various reading resources and enrich library’s book collections. This study employed RnD method which is Analyze, Design, and Develop. It involves 12 schools and 40 junior high school students and uses a questionnaire to analyze the needs. For the design and development phase, it uses an online platform called Kodular to create the digital library. The result of this study is the product of an Android application called Digilib Komulit that can unite and access various reading source websites through one application and can be used in schools’ library as multimedia collection.